PENGARUH KOMITMEN ORGANISASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PT. BPRS GUNUNG SLAMET CILACAP - Nurul Hasanah; Guntoro; Neela Sarifatul Zanah (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
This research takes the title â€œThe Influence of Organizational Commitment, Work Discipline and Non-Physical Work Environment on the Performance of Employees of PT. BPRS Gunung Slamet Cilacapâ€, the formulation of the problem is whether Organizational Commitment, Work Discipline and Non-Physical Work Environment affect the Performance of Employees of PT. BPRS Gunung Slamet Cilacap? and the purpose of this study is to analyze the effect of organizational commitment, work discipline and non-physical work environment on employee performance at PT. SRB Gunung Slamet Cilacap. This research method is a type of quantitative research using survey methods in obtaining the required data, namely by giving questionnaires to respondents at PT. SRB Gunung Slamet Cilacap. The data analysis technique uses Multiple Linear Regression Analysis, Coefficient of Determination Analysis and t-test (Partial Test). Results The conclusion based on the results of multiple linear regression equations obtained from the calculation of Y = 0.754 + 0.447 X1 + 0.353 X2 + 0.285 X3 is: The tcount value of the Organizational Commitment variable (X1) is greater than the ttable value (3.732 > 2.056). The tcount value of the Work Discipline variable (X2) is greater than the ttable value (2,431 > 2,056). The tcount value of the Non-Physical Work Environment (X3) variable is greater than the ttable value (2.718 > 2.056). Therefore, the three hypotheses affect the performance of employees of PT. BPRS Gunung Slamet Cilacap